Optimization of repeat plerixafor dosing for autologous peripheral blood stem-cell collection. (June 2021) - Gupta, Gaurav K.; Perreault, Sarah; Seropian, Stuart E.; Tormey, Christopher A.; Hendrickson, Jeanne E.
Abstract: Introduction: Peripheral CD34+ cells may be mobilized using filgrastim alone or in combination with chemotherapy. The addition of plerixafor can be efficacious, though guidelines for repeat dosing are lacking. Material and Methods: This quality improvement project was initiated to generate guidelines for repeat plerixafor dosing after retrospective evaluation of data in adult patients undergoing autologous peripheral blood stem cell mobilization and collection. Results: Analysis included 195 patients: 119 (61 %) with multiple myeloma and 76 (39 %) with lymphoma. Patients given at least one dose of plerixafor (n = 109) were further divided: Group 1 ) (A) goal of 3 × 10E6/kg and day 1 peripheral blood CD34+ count < 30 × 10E6/L, vs (B) ≥ 30 × 10 E6/L; Group 2 ) (A) goal of 6 × 10E6/kg and day 1 peripheral blood CD34+ count < 50 × 10E6/L or < 50 % of collection goal after day 1, vs (B) ≥ 50 % of collection goal after day 1. Ninety five percent of cases in Group 1B and 88 % of cases in Group 2B did not receive additional plerixafor doses and all of them achieved their collection goals. In contrast, those in Groups 1A and 2A required additional plerixafor dosing and some mobilizations/collections were futile. Conclusion: Based on these data, with consideration of collection goal, peripheral blood CD34+ count, and CD34+ cell bag count on collection day 1, we have generated institutional guidelines for collection initiation and repeat plerixafor dosing. Long term, we predict these guidelines will optimize pharmacy, apheresis, and stem cell processing resources while improving the patient experience.